PTU-148 A large prospective audit of morbidity and mortality associated with feeding gastrostomies in the community. (22nd June 2015) - Clarke, E; Chudleigh, V; Pitts, N; Latchford, A; Lewis, S
Abstract : Introduction: Morbidity after 30 days and morbidity after 1 year from gastrostomy placement is poorly characterised as patients are discharged into the community. We prospectively recorded morbidity and mortality associated with gastrostomy placement over a five year period. Method: Community dietitians regularly reviewed all patients with a gastrostomy after hospital discharge, prospectively recording morbidity and mortality between 2008–2012. In addition hospital databases and case notes were examined. Recorded morbidity included insertion site infection, leakage, over granulation, haemorrhage and buried bumper. Results: There were no deaths and few complications directly related to gastrostomy insertion in 350 patients. We collected a total of 571 years of gastrostomy data. Mortality within 10 days was predominantly from a respiratory cause. 30 day, 3 and 21 month cumulative mortality (and morbidity) were 8% (2%), 16% (10%) and 35% (15%) respectively. 38% of patients required treatment for an insertion site infection with 70% of these having further infections. Overall there was a site infection every 2.1 years a gastrostomy was in situ . Complications such as buried bumpers, persistent fistulas and overgranulation were rare. Few gastrostomies required replacement (11%). Conclusion: This is the first prospective study of morbidity and mortality in a large number of patients undergoing gastrostomy placement over an extended period of time. We have demonstrated reassuringly low rates of gastrostomy-associated morbidity and mortality. There was no direct mortality. The greatest morbidity resulted from gastrostomy-site infection. Disclosure of interest: None Declared. References: Dennis MS, Lewis SC, Warlow C, FOOD Trial Collaboration. Effect of timing and method of enteral tube feeding for dysphagic stroke patients (FOOD): a multicentre randomised controlled trial. Lancet 2005:365(9461):764–772 Johnston SD, et al . Death after PEG: results of the national confidential enquiry into patient outcome and death. Gastrointest Endosc. 2008;68(2):223–227 Mitchell SL, et al . The risk factors and impact on survival of feeding tube placement in nursing home residents with severe cognitive impairment. Arch Intern Med. 1997;157(3):337–332 Sheehan JJ. Percutaneous endoscopic gastrostomy. Irish Med J. 2003;96(9) Westaby D, et al . The provision of a percutaneously placed enteral tube feeding service. Gut 2010;59:1592–1605 Wilcox CM, McClave SA. To peg or not to peg. Clin Gastroenterol Hepatol. 2013;11(11):1451–1452